Assessing the level of resilience of enterprises as a precondition for ensuring their sustainability and competitiveness - Ligonenko, Larysa; Andriichuk, Vasyl; Melnyk, Serhii; Smyrnov, Yevhen (Technology audit and production reserves, 2025)
The object of research is the resilience of industrial enterprises of Ukraine in a crisis environment (martial law), which is a prerequisite for ensuring their stability and competitiveness. One of the significant limitations is the imperfection of existing resilience assessment systems. Existing methodological approaches do not allow for a general assessment of its level, identifying weaknesses and problems. To eliminate these shortcomings, a functional-integration approach to assessing the level of resilience of enterprises is proposed, which covers four key areas: production, sales, personnel and financial. The proposed approach involves assessing the level of functional types of resilience, which subsequently form an integral assessment of the level of resilience. The information base is the balance sheet indices of economic activity, which are calculated based on a survey of enterprises on the dynamics of more than 20 indicators of their economic and financial activities. A study of the monthly dynamics of the level of functional and integral resilience in 2023–2024 showed that the food industry, which ensures the production of essential goods, is the most resistant to crisis impacts. The resilience of chemical industry enterprises is growing steadily, which indicates an increase in demand for its products and adaptation to the realities of wartime. Enterprises in other industries are characterized by significant fluctuations in resilience, which indicates the need for additional measures to ensure it at the proper level. The integral assessment of the level of resilience of industrial enterprises of Ukraine in November 2024 is +0.05, which indicates their adaptation to current business conditions. The highest level of resilience is demonstrated by the food and printing industries, while metallurgy and mechanical engineering remain more vulnerable to the challenges of wartime. The main problems affecting the resilience of enterprises have been identified: disruptions in the supply of raw materials, instability of demand, personnel difficulties and financial risks. The development of focused management influences (diversification of sales markets, support for export activities and investments in personnel development) will contribute to a faster restoration of their stability and competitiveness.